Evaluation of Nutritional Status of Children with Autism Spectrum Disorder Receiving Daytime Rehabilitation - İSLAMOĞLU, AYŞE HÜMEYRA; SABUNCULAR, GÜLEREN; ÇELİK, ZEHRA MARGOT; AKTAÇ, ŞULE (My University, 2024)
Objective: The aim of this study was to evaluate the nutritional status, eating habits and behavior of children with autism spectrum disorder. Methods: This observational study included 109 individuals from Istanbul diagnosed with autism spectrum disorder aged 3-18 years; the patients were receiving daytime rehabilitation. A questionnaire including socio-demographic characteristics, nutritional behavior and eating habits of participants was applied by face-to-face interview method, anthropometric measurements (body weight and height) and food consumption records were taken, using a 24-hour dietary recall taken by the researchers. Results: Of all, 66.1% (n=72) of the participants were male. It was determined that 16.2% (n=6) of the female participants were overweight and 27.0% (n=10) were obese, while 33.3% (n=24) of the male participants were overweight and 29.2% (n=21) were obese. The rate of food selectivity was found to be 59.6%; 28.4% of the participants received additional support during mealtimes, 13.8% followed various special diets, including gluten-free and casein-free diets. Most of the participants’ energy intake (60.6%), vitamin D (100.0%) and calcium (71.6%) were below reference values. The majority of the participants’ vitamin A (92.7%) and sodium (92.7%) intakes were above the recommended values. Conclusion: The findings of the study reveal that children and adolescents with autism spectrum disorder have high rates of obesity and food selectivity. The need for additional support at mealtimes, and the inadequate or excessive intake of nutrients are among other nutrition-related problems faced by this population. Keywords: Nutrition, children, autism spectrum disorder

Amaç: Bu çalışmada, otizm spektrum bozukluğu olan çocukların beslenme durumlarının, yeme alışkanlıklarının ve davranışlarının değerlendirilmesi amaçlanmıştır. Gereç ve Yöntem: Bu gözlemsel çalışmaya İstanbul’da gündüzlü rehabilitasyon gören, 3-18 yaş arası, otizm spektrum bozukluğu olan 109 birey dahil edilmiştir. Katılımcılara yüz yüze görüşme metoduyla sosyo-demografik özellikleri, beslenme davranışları ve yemek yeme alışkanlıklarını içeren bir anket uygulanmış, antropometrik ölçümleri (vücut ağırlığı ve boy uzunluğu) ve 24 saatlik hatırlatma yöntemi ile besin tüketim kayıtları araştırmacılar tarafından alınmıştır. Bulgular: Yüz dokuz katılımcının %66,1 (n=72)’inin erkek olduğu saptanmıştır. Kızların %16,2 (n=6)’sinin hafif şişman, %27,0 (n=10)’sinin obez olduğu, erkek katılımcıların ise %33,3 (n=24)’ünün hafif şişman ve %29,2 (n=21)’sinin obez olduğu belirlenmiştir. Katılımcılarda, besin seçicilik oranı %59,6 olarak bulunmuş ve katılımcıların %28,4’ü öğün zamanlarında ek destek aldığı, %13,8’i glütensiz ve kazeinsiz diyet de dahil olmak üzere çeşitli özel diyetler uyguladığı belirlenmiştir. Katılımcıların çoğunun enerji (%60,6), D vitamini (%100,0) ve kalsiyum (%71,6) alımları referans değerlerin altında; A vitamini (%92,7) ve sodyum (%92,7) alımları önerilen değerlerin üzerinde bulunmuştur. Sonuç: Çalışmanın bulguları, Otizm Spektrum Bozukluğu olan çocuk ve adölesanlarda yüksek oranda obezite ve besin seçiciliği olduğunu ortaya koymaktadır. Öğün zamanlarında ek desteğe ihtiyaç duyulması, yetersiz veya fazla besin ögesi alımı, bu popülasyonun karşılaştığı diğer beslenme ile ilintili sorunlar arasındadır. Anahtar Kelimeler: Beslenme, çocuk, otizm spektrum bozukluğu
Gündüzlü Rehabilitasyon Gören Otizm Spektrum Bozukluğu Olan Çocukların Beslenme Durumlarının Değerlendirilmesi
Keywords: Beslenme; çocuk; otizm spektrum bozukluğu; Nutrition; children; autism spectrum disorder